2017
DOI: 10.1080/20008686.2017.1328964
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing prevalence of transmitted drug resistance among ART-naive HIV-1-infected patients in Iceland, 1996–2012

Abstract: Introduction: Resistance to antiretroviral drugs can complicate the management of HIV-1 infection and impair control of its spread. The aim of the current study was to investigate the prevalence and transmission of HIV-1 drug resistance among 106 antiretroviral therapy (ART)-naïve patients diagnosed in Iceland (1996–2012). Methods: HIV-1 polymerase sequences were analysed using the Calibrated Population Resistance tool. Domestic spread of transmitted drug resistance (TDR) was investigated through maximum likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…No significant differences were observed between the prevalence of TDR and demographic characteristic, which was similar with a previous study [ 36 , 37 ]. Many studies reported that the higher prevalence of TDR among MSM compared to heterosexuals; interestingly, the opposite results also were found in others reports [ 38 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…No significant differences were observed between the prevalence of TDR and demographic characteristic, which was similar with a previous study [ 36 , 37 ]. Many studies reported that the higher prevalence of TDR among MSM compared to heterosexuals; interestingly, the opposite results also were found in others reports [ 38 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Africa had the highest number of articles identified in the search of any region (n=30) . However, the European region had the highest number of participants for analysis of pretreatment resistance mutations (n=33,957 for NRTI-associated mutations; n=34,201 for NNRTI-associated mutations) [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60], and Southeast Asia had the highest number of participants for analysis of acquired resistance mutations (n=26,772 for NRTI-associated mutations; 26,568 for NNRTI-associated mutations) [61][62][63][64][65][66][67][68][69].…”
Section: Search Resultsmentioning
confidence: 99%
“…The estimated global prevalence of pretreatment DRMs was 4% (n=2,719/60,567; range, 2% [Asia Pacific] to 6% [North America]) for those associated with NRTI resistance [16,18,25,28,[30][31][32][35][36][37][38]40,43,44,46,48,49,[51][52][53][54][55][56][57][58][59][60] and 6% (n=3,605/61,402; range, 3% [Asia Pacific] to 8% [Africa and North America]) for those associated with resistance to any NNRTI (Figure 1) [16,18,25,28,[30][31][32][33][34][35][36][37][38][39]41,[70][71][72][73][74][75]…”
Section: Global Prevalence Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [12], viral load, symptoms, CD4 counts, transmission route, and the duration of ART are associated with HIV-1 DR. Resistance to antiretroviral drugs can complicate the management of HIV-1infection and impair control of its spread. Screening for TDF is recommended to limit its local spread and to optimize HIV-1 therapy [13]. Test-and-treat programs are central to the global control of HIV, but transmitted drug resistance threatens the effectiveness of these programs [14].…”
Section: Introductionmentioning
confidence: 99%